Procedure-Specific Effectiveness of Warmed Versus Room-Temperature Irrigation Fluids for Preventing Perioperative Hypothermia: A Systematic Review - Harlasgunawan, Alia Rahmi; Kosasih, Cecep Eli; Nuraeni, Aan (Journal of Health and Nutrition Research, 2025)
This study investigates the impact of using warmed irrigation fluid over room-temperature fluid on patient body temperature during surgery, while also exploring the variables that influence its effectiveness. Systematic review following PRISMA guidelines. Comprehensive searches were conducted in PubMed/MEDLINE, Embase, Cochrane Central, and Web of Science (inception to March 2024) using PICO framework-derived search terms. Inclusion criteria: randomized controlled trials (RCTs) and systematic reviews comparing warmed irrigation fluids (≥36°C) versus room temperature in adult surgical patients. Quality assessment used Joanna Briggs Institute (JBI) critical appraisal tools. Data synthesis included descriptive analysis and meta-analysis where appropriate. Ten studies (eight randomized controlled trials and two systematic reviews/meta-analyses) met inclusion criteria, comprising 2,459 participants across various surgical procedures. Overall methodological quality was high (mean JBI score 10.2/11, 93%). Effectiveness analysis revealed that 67% of individual studies (6/9) demonstrated significant benefits, with clear procedure-specific patterns. Arthroscopic shoulder surgery showed the highest success rate (75%, 3/4 studies) with effect sizes of 67–80% reduction in hypothermia incidence when using 37°C irrigation. TURP procedures demonstrated conditional effectiveness (50% success rate) depending on anesthesia type, while laparoscopic surgery showed no benefit (0% success rate) due to competing heat loss mechanisms. Warmed irrigation fluids at 37°C demonstrate procedure-specific effectiveness, with arthroscopic shoulder surgery showing highest success rates (75%) and laparoscopic surgery showing no benefit.